Synthesis and antifungal activity of some substituted phenothiazines and related compounds - Sarmiento, Gabriela Pabla (2011)
Several phenothiazines and related compounds were synthesized and their antifungal activity was evaluated in vitro. The results observed for α-chloro-N-acetyl phenothiazine led us to choose this compound as a lead in the search of antifungal agents.